Genetics and Clinical Features of Noncompaction Cardiomyopathy in the Fetal Population - Sun, Hairui; Hao, Xiaoyan; Wang, Xin; Zhou, Xiaoxue; Zhang, Ye; Liu, Xiaowei; Han, Jiancheng; Gu, Xiaoyan; Sun, Lin; Zhao, Ying; Yi, Tong; Zhang, Hongjia; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Noncompaction Cardiomyopathy (NCCM) has been classified as primary genetic cardiomyopathy and has gained increasing clinical awareness; however, little is known about NCCM in the fetal population. We aimed to investigate the clinical characteristics and genetic spectrum of a fetal population with NCCM. Methods: We retrospectively reviewed all fetuses with a prenatal diagnosis of NCCM at a single center between October 2010 to December 2019. These cases were investigated for gestational age at diagnosis, gender, left or biventricular involvement, associated cardiac phenotypes, outcomes, and genetic testing data. Results: We identified 37 fetuses with NCCM out of 49,898 fetuses, indicating that the incidence of NCCM in the fetal population was 0.07%. Of the 37 fetuses, 26 were male, ten were female and one was of unknown gender. NCCM involvement biventricle is the most common (n=16, 43%), followed by confined to the left ventricle (n=14, 38%). 19 (51%) had additional congenital heart defects, with right-sided lesions being the most common (n=14, 74%), followed by ventricular septal defects (n=10, 53%). Hydrops fetalis was present in 12 cases (32%), of which four were atypical (pericardial effusion only). Sequencing analysis was performed at autopsy (n=19) or postnatally (n=1) on 20 fetuses. Of the 20 fetuses undergoing copy number variation sequencing and whole-exome sequencing, nine (47%) had positive genetic results, including one with a pathogenic copy number variant and eight with pathogenic/likely pathogenic variants. Non-sarcomere gene mutations accounted for the vast majority (n=7). In contrast, sarcomere gene mutations occurred in only one case (TPM1), and no mutations were identified in the three most common sarcomere genes (MYH7, TTN, and MYBPC3) of pediatric and adult patients. Pathogenic/likely pathogenic variants were significantly more frequent in fetuses with congenital heart defects than those without congenital heart defects. Conclusions: Our data demonstrate that fetal NCCM is a unique entity. Compared with pediatric and adult NCCM, fetal NCCM is more prone to biventricle involvement, more likely to be complicated with congenital heart defects, and has a distinct genetic spectrum.